Analysis of the Impact of Macroeconomic Variable Volatility on Equity Mutual Fund Net Asset Value in Indonesia - Kemala Dewi; Tri Wahyu Rejekiningsih (Jurnal Ekonomi dan Bisnis Digital, 2025)
This research investigates the effect of interest rate volatility, exchange rate volatility, and competitor stock price volatility on the performance of equity mutual funds in Indonesia. Monthly data from January 2013 to December 2023 were analyzed using ARCH–GARCH models to measure volatility and the ARDL approach to assess relationships. The results reveal that interest rate and competitor stock price volatility significantly reduce NAV, while exchange rate volatility show no immediate effect, suggesting a delayed adjustment. These findings contribute to understanding how macroeconomic and market factors influence mutual fund performance and provide insights for fund managers and investors in developing strategies to navigate volatile market conditions.